МАТЕМАТИЧНА МОДЕЛЬ ДЛЯ АНАЛІЗУ ПЕРЕХІДНИХ ПРОЦЕСІВ В ДВООБВИТКОВИХ ТРАНСФОРМАТОРАХ У МЕТОДІ ПРЯМИХ - Сегеда, М.С.; Гоголюк, П.Ф.; Близнак, Ю.В. (Інститут електродинаміки НАН України, Київ, 2022)
A mathematical model of a two-winding transformer for research of fast transient processes in windings in the form of an electromagnetic circuit, taking into account the main magnetic flux, own and mutual interturns and interwinding dissipation fluxes, transverse turns and longitudinal interwinding capacitances of the winding, is developed by using the straights method. The created model simplifies engineering calculations of fast transient processes in windings by applying the methods of the theory of electromagnetic circuits instead of the methods of mathematical physics, which are difficult for practical application. Transient processes and voltage distribution in transformer windings, under the action of pulse overvoltage in the form of a standardized pulse, are researched. References 8, figures 4.